The Role of Water User Farmers Associations (P3A) in Improving Irrigation Network Performance in the Patawang - Ema Aisyah Fadila Ambuwaru; Ramzy G.G.L. Sayonara; Amandus Jong Tallo (Jurnal Teknologi Riset Terapan, 2025)
Purpose: Water User Farmers Associations (P3A) manage tertiary irrigation systems in Indonesia, yet the relative importance of technical capability versus service quality for irrigation performance remains unclear. This study examines the effects of P3A technical capability and service quality on irrigation performance in Patawang, East Sumba.Research Methodology: Research used quantitative descriptive correlational design. Data from 33 respondents across 11 P3A organisations were selected by sampling. Variables include irrigation performance (Y), technical capability (X1), and service quality (X2). Data were analysed using multiple linear regression in SPSS with validity, reliability, and assumption tests.Results: The multiple linear regression model was significant (F = 7.904, F-table = 3.32, p = 0.002). R² = 0.345 indicates 34.5% explanatory power. P3A Technical Capability significantly affects performance (? = 0.631, t = 2.803, p = 0.009), while Service Quality is not significant (? = ?0.146, t = ?0.488, p = 0.629). Equation: Y = 12.341 + 0.631X1 ? 0.146X2Conclusions: P3A technical capability is the main determinant of irrigation performance in irrigation performance while service quality is not significant. Strengthening technical capacity through training in water management, canal maintenance, and scheduling is the priority for sustainable irrigation improvement. Limitations: Limited to respondents reducing generalisability Model explains 34.5% variance other factors such as infrastructure coordination and funding were not included. Contributions: Provides evidence on P3A capability versus service quality effects in Eastern Indonesia irrigation management.